Temporal Shifts in Understanding of Privacy: Perspectives of House Users in Baghdad During Two Different Periods: Case Studies in Selected Neighborhoods (Journal of Engineering, 2026)
The Dwelling is a Fundamental issue related to human beings; throughout time, man has always had to dwell in a place and build his house. Due to different styles and typologies appearing all over the world, all containing the character of privacy as the main element of human life in their dwellings. The present study aims to investigate the temporal shift in understanding privacy during the 20th and 21st centuries in Baghdadi houses, and what are the physical elements that are related to the meaning of privacy? The research methodology analyzed the concepts of privacy to extract the research indicators to be applied to (49) samples of individual houses in selected neighborhoods in two different periods. The data was collected from visual surveys and checklist observations that the researchers conducted with 90 Iraqi residents living in those design types and styles. The results indicated that privacy resembles a balanced physical treatment interrelated to social considerations planning, ranging from space designs to the details, which results in organizing the individual’s interactions with the family and then the family's interaction with others, mainly the neighbors. Each one of them has its own design and planning requirements. The results showed increased privacy features and approaching (isolation) in the contemporary Baghdadi house (after 2003) due to the change in the social nature of neighborhood members and a decreased sense of security. The research noted that there are planning indicators associated with an increased sense of privacy, such as the width of the residential street, the residential nature of the neighborhood, and the nonexistence of a neighbor across from the house.